Body, Gender, Senses: Subversive Expressions in Early Modern Art and Literature - Franzén, Carin; Vernqvist, Johanna (De Gruyter, 2024)
This volume explores through a series of essays, subversive expressions of body, gender and senses in literature and art by early modern women poets, philosophers, and artists. Underlining the critical relations between emotions, perception, and reason it traces from Italy and Spain to France and Sweden, other forms of subjectivity than the ones usually related to the early modern period’s subjectivation of female bodies, thinking and desires.